2017
DOI: 10.1177/1099636217707933
|View full text |Cite
|
Sign up to set email alerts
|

On vibration isolation of sandwich plate with periodic hollow tube core

Abstract: The vibration isolation performance of a PC sandwich plate with periodic hollow tube core is investigated experimentally and numerically. The experiment results reveal that there exist vibration attenuation zones in acceleration frequency responses which can be improved by increasing the number of periods or tuning some structure parameters. The presence of soft fillers shifts the attenuation zone to lower frequencies and enhances the capability of vibration isolation to some extent. Dispersion relations and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…[3] Conducted system work for mechanic performance of very light sandwich plate with frictional pyramid core. Besides, sandwich structure could be applied to reduce structural vibration and noise level by selecting reasonable core material [4][5]. For a sandwich shell, the final design is to be made for good vibration and noise reduction.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Conducted system work for mechanic performance of very light sandwich plate with frictional pyramid core. Besides, sandwich structure could be applied to reduce structural vibration and noise level by selecting reasonable core material [4][5]. For a sandwich shell, the final design is to be made for good vibration and noise reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, FADs can be designed to meet the vibration isolation frequency requirements in practical engineering to protect the building. In recent years, many scholars have studied the theory and application of periodic wave barriers, such as periodic piles (Cheng et al., 2013; Liu, Qin, & Yu, 2020; Meng & Shi, 2019), periodic walls (Huang et al., 2017; Marfia & Sacco, 2012), periodic lattice sandwich panels (Yu & Miao, 2019), which can all be used in the real‐life civil/infrastructure engineering to attenuate vibrations caused by cars, railways, subways, or earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the sound insulation of sandwich structures improved significantly because of the stop band design of the sandwich plates. Recently, Yu and Miao (2019) numerically and experimentally studied the vibration isolation performance of a phononic crystal sandwich plate with periodic hollow tube core. Results showed that the proposed periodic sandwich structures could possess excellent attenuation performances of structural vibration because of the Bragg scatter band gap characteristics of periodic sandwich structures.…”
Section: Introductionmentioning
confidence: 99%